Dynamical evolution of titanium, strontium, and yttrium spots on the surface of the HgMn star HD11753 - Briquet, M. (2010)
Aims: We gathered about 100 high-resolution spectra of three typical HgMn (mercury-manganese) stars, HD11753, HD53244, and HD221507, to search for slowly pulsating B-like pulsations and surface inhomogeneous distribution of various chemical elements. Methods: Classical frequency analysis methods were used to detect line profile variability and to determine the variation period. Doppler imaging reconstruction was performed to obtain abundance maps of chemical elements on the stellar surface. Results: For HD11753, which is the star with the most pronounced variability, distinct spectral line profile changes were detected for Ti, Sr, Y, Zr, and Hg, whereas for HD53244 and HD221507 the most variable line profiles belong to the elements Hg and Y, respectively. We derived rotation periods for all three stars from the variations of radial velocities and equivalent widths of spectral lines belonging to inhomogeneously distributed elements: Prot (HD11753) = 9.54 d, Prot (HD53244) = 6.16 d, and Prot (HD221507) = 1.93 d. For HD11753 the Doppler imaging technique was applied to derive the distribution of the most variable elements Ti, Sr, and Y using two datasets separated by ∼65 days. Results of Doppler imaging reconstruction revealed noticeable changes in the surface distributions of Ti II, Sr II, and Y II between the datasets, indicating the hitherto not well understood physical processes in stars with radiative envelopes that cause a rather fast dynamical chemical spot evolution.